Abnormal lung ultrasound pattern during labor: A prospective cohort pilot study. Issue 5 (6th February 2019) - Krawczyk, Paweł; Jastrzębska, Agnieszka; Sałapa, Kinga; Szczeklik, Wojciech; Andres, Janusz
Abstract: Purpose: Lung ultrasound (LUS) examination is used to evaluate patients with acute respiratory failure. The physiological LUS pattern during labor in healthy parturients has not been well described. The aim of this study was to evaluate the LUS pattern in a cohort of healthy women during uncomplicated labor. Methods: We used the 8‐point LUS assessment protocol and investigated lung sliding, A‐lines, B‐lines, interstitial syndrome, lung consolidation, and pleural effusion according to the International Consensus Document with two additional supradiaphragmatic projections. All patients were screened twice; once during the first stage of labor and again within 2 hours after delivery. Results: We included 24 patients in this study from February 2014 to August 2015. A total of 480 LUS records were retained for further analysis. Overall, 16 of 24 patients (67%) had at least one positive region (three or more B‐lines) during the peridelivery LUS evaluation. Interstitial syndrome was detected in five patients (21%). There were no differences in A‐line ( P = 0.38) or B‐line ( P = 0.68) prevalence between LUS examinations before and after delivery. Conclusions: Women in uncomplicated labor can present abnormal LUS findings, which may affect the interpretation of LUS results in patients with respiratory deterioration. Further studies should address this topic in larger cohort of patients.